2017
DOI: 10.1016/j.molliq.2017.01.053
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilicity and flexibility of the spacer as critical parameters on the aggregation behavior of long alkyl chain cationic gemini surfactants in aqueous solution

Abstract: Series of quaternary ammonium-based gemini surfactants with long alkyl chains (C12 and C18) containing different spacers and substituents attached to the polar head group have been synthesized and their aggregation properties in aqueous solution examined. The effect of the hydrophobic chain, the nature and structure of the spacer group and the polarity of the head group on the aggregation behavior of such dimeric surfactants has been investigated. The critical micelle concentration (cmc) values of gemini surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 59 publications
11
47
0
Order By: Relevance
“…The γ ‐lg c curve of MCTS was shown in Figure , and the relevant surface activity parameters are given in Table . As shown in Table , we found that the CMC of the surfactant solution is merely 0.064 g L‐1, and the corresponding surface tension of the solution is 38.85 mN m‐1 at 298 K, which is lower than that of the Gemini surfactants . In brief, it may be explained by that the MCTS formed the cross‐linked network by the intermolecular and intramolecular hydrogen bonds (Figure ), which made molecules closer and facilitate the adsorption of surfactants at the surface of the solution and decrease the CMC.…”
Section: Resultsmentioning
confidence: 88%
“…The γ ‐lg c curve of MCTS was shown in Figure , and the relevant surface activity parameters are given in Table . As shown in Table , we found that the CMC of the surfactant solution is merely 0.064 g L‐1, and the corresponding surface tension of the solution is 38.85 mN m‐1 at 298 K, which is lower than that of the Gemini surfactants . In brief, it may be explained by that the MCTS formed the cross‐linked network by the intermolecular and intramolecular hydrogen bonds (Figure ), which made molecules closer and facilitate the adsorption of surfactants at the surface of the solution and decrease the CMC.…”
Section: Resultsmentioning
confidence: 88%
“…As illustrated in Fig. , the minimum value of I 1 /I 3 is decreased with the increment of the hydrophobic alkyl chain length, implying that the longer alkyl tail leads to the palisade layer more compact and has a reduction for polarity (Garcia et al, ; Martin et al, ). It can be clearly noticed from Table that the obtained values of CMC are 1.93, 0.352, and 0.311 mmol L −1 for 3C 8 taDA, 3C 10 taDA, and 3C 12 taDA, respectively, which are in accordance with those obtained from surface tension measurements at 298.15 K.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the conductivity and SPQ fluorescence probe methods are summarized in Table 1. DLS measurements have been conducted to estimate the hydrodynamic diameter of the aggregates 20,21 .…”
Section: Resultsmentioning
confidence: 99%